Histone Deacetylase Inhibitor Tributyrin and Vitamin A in Cancer - Heidor, Renato (2017)
Bioactive food compounds like vitamin A and the butyrate’s prodrug tributyrin have preventive activities against different types of cancer, and their use in association could represent a promising strategy for cancer treatment and che- moprevention. Both compounds can induce cell differentiation and apoptosis of neoplastic and preneoplastic cells by means of modulation of gene transcription, yet they act through different but interconnected mechanisms. Vitamin A acts through nuclear receptors that are tightly regulated by histone modifications such as acetylation and DNA methylation. Tributyrin modulates transcription of genes by HDACs inhibition and histone hyperacetylation. This chapter describes how epigenetics mediates the antineoplastic and chemopreventive activity of vitamin A, tributyrin, and their derivatives and how their combination can be used to help overcome current limitations in cancer treatment and prevention. We also show how the mechanisms of action of vitamin A and tributyrin have aided in the development of synthetic and bioengineered compounds like synthetic retinoids and structured lipids, respectively.